El acceso a la justicia y las nuevas tecnologías aplicadas durante la ejecución de las penas de prisión - Ishiy, Karla Tayumi; Marcondes Ramos, José Ricardo (Revista de Estudios Jurídicos y Criminológicos, 2023)
The aim is to analyse the current developments of prison tech, verify its progress in promoting the access to justice in the prison context, examine the digital transformation in the Portuguese context and raise the ethical, practical and human rights issues that the use of technologies in prisons raises. This essay is oriented by the following question: Are technological advances serving as a tool to support or further to discriminate against persons deprived of their liberty in their access to justice?